Commodification Of Cultural Identity: A Qualitative Visual Analysis Of The Semar Figure In Trademark Logos - Yayah Rukiah; Ranang Agung Sugihartono; Sarwanto; Sunardi (FAKULTAS DAKWAH UIN SALATIGA, 2026)
Logos are important identity markers in a trademark. This becomes interesting when many local trademarks originating from Central Java use the figure of Semar in their logos. Through observation on trademark registration sites, there are 208 trademarks that use the figure of Semar in their logos, with 108 of them officially registered. This study examines how the mythological figure of Semar is transformed and interpreted as a modern visual identity through the approach of Stuart Hall's theory of representation and identity, as well as Gillian Rose's visual methodology in the realm of the site of audiencing. The research analyzed several logos taken based on purposive sampling, then discussed in detail the visuals of the logos that contain deep historical and social significance. The results of the analysis show that the shift in medium from shadow puppets to logos changes the mechanism of audience meaning, from a narrative-pedagogical approach to instant and associative visual recognition. The use of the figure of Semar in trademark logos is not merely an aesthetic strategy, but a representational practice that negotiates Javanese cultural identity in the contemporary public space. This article concludes that the cultural identity represented by Semar is not static, but is continuously reconstructed by the audience to build emotional bonds and cultural legitimacy amid the dynamics of modernization, one of which is through cultural commodification in the form of trademark logos.